Archaeological excavations in the Holy Sepulchre, Jerusalem: 2024 preliminary report - Stasolla, Francesca Romana (Liber annuus, 2024)
Aim of the contribution is the presentation of the results of the 2024 archeological excavations conducted by a team of the University of Rome Sapienza inside the Basilica of the Holy Sepulchre in Jerusalem, as part of a project to restore the floor of the complex. Investigations covered areas of the entrance, the south-eastern deambulatory, the Franciscan possession. These findings contribute to the reconstruction of the archaeological history of the towns and the architectural phases of the Holy Sepulchre complex. The 2024 research provided greater elucidation above all the pre-Christian phases of the complex, as well as bringing to light more specific subsequent contexts. It has been confirmed that the quarry extends over the entire area of the current church and may be found everywhere below the later structures; its exploitation appears prolonged in time. Some reflexions on the Roman topography of the area of the Holy Sepulchre are proposed and some hypotheses are moved forward the constitution of the Christian complex. The long life of the Holy Sepulcher emerges, with constructions and reconstructions over the centuries.